2015
DOI: 10.1080/09168451.2015.1069701
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic study of the quenching reaction of singlet oxygen by seven rice bran extracts in ethanol solution. Development of a singlet oxygen absorption capacity (SOAC) assay method

Abstract: Measurements of singlet oxygen ((1)O2) quenching rates (kQ (S)) and the relative singlet oxygen absorption capacity (SOAC) values were performed for seven rice bran extracts 1-7, which contained different concentrations of antioxidants (AOs) (such as α-, β-, γ-, and δ-tocopherols and -tocotrienols, three carotenoids (lutein, β-carotene, and zeaxanthin), and γ-oryzanol), in ethanol at 35 °C using UV-vis spectrophotometry. The concentrations of four tocopherols and four tocotrienols, three carotenoids, and γ-ory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 49 publications
2
13
0
Order By: Relevance
“…α-Tocopherol (α-Toc) is used as a standard antioxidant in the SOAC assay, and the antioxidant capacity of a sample is expressed as a value relative to that of α-Toc. This method allows evaluation of the singlet oxygen absorption capacity of both hydrophilic and lipophilic antioxidants in a variety of food extract such as from vegetables, fruits, and edible oils (Aizawa et al, 2011;Mukai et al, 2012;Iwasaki et al, 2015;Mukai et al, 2015). Moreover, the SOAC values of food extracts are nearly equal to theoretical values calculated from each SOAC value of antioxidants contained in these food extracts (Aizawa et al, 2011).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…α-Tocopherol (α-Toc) is used as a standard antioxidant in the SOAC assay, and the antioxidant capacity of a sample is expressed as a value relative to that of α-Toc. This method allows evaluation of the singlet oxygen absorption capacity of both hydrophilic and lipophilic antioxidants in a variety of food extract such as from vegetables, fruits, and edible oils (Aizawa et al, 2011;Mukai et al, 2012;Iwasaki et al, 2015;Mukai et al, 2015). Moreover, the SOAC values of food extracts are nearly equal to theoretical values calculated from each SOAC value of antioxidants contained in these food extracts (Aizawa et al, 2011).…”
Section: Introductionmentioning
confidence: 98%
“…Hama et al (2012) reported that astaxanthin prevented UV-induced skin damage by scavenging singlet oxygen production, and Li et al (2010) showed that zeaxanthin and lutein prevented the light-induced production of singlet oxygen in human retinal pigment epithelium/choroid. Singlet oxygen absorption capacity (SOAC) is an in vitro assay method used to evaluate the singlet oxygen quenching capacity of a sample and was developed by Mukai et al, 2015;Ouchi et al, 2010;Aizawa et al, 2011;Mukai et al, 2012;Iwasaki et al, 2015. This method measures absorption capacity for singlet oxygen induced by the thermal decomposition of 4-methyl-1,4-etheno-2,3-benzodioxin-1(4H)-propanoic acid (endoperoxide, EP) at 35℃ using 2,5-diphenyl-3,4-benzofuran (DPBF) as a UV-Vis absorption probe. Time course changes in the absorption at 413 nm of DPBF are observed using a UV-Vis spectrophotometer equipped with a six-channel cell positioner.…”
Section: Introductionmentioning
confidence: 99%
“…Vitamin E homologues (i.e. d-a-, b-, g-, d-tocopherol and -tocotrienol (a-, b-, g-, d-Toc and -Toc-3)) can act as an efficient quencher of 1 O2 (27,28). It was shown that a-Toc quenches 1 O2 by a combination of physical quenching (kq) and chemical reaction (chemical quenching, kr).…”
mentioning
confidence: 99%
“…(1)) (29). kQ 1 O21Tocopherol→ physical quenching (kq) 1chemical reaction (k r) (kQ5kq1kr) (1) As general phenolic AOs are easily soluble in ethanol, measurements of kQ values were performed in ethanol, in previous works (27,28). On the other hand, carotenoids (Cars) generally show low (or very low) solubility in ethanol, and, thus, ethanol/chloroform/D2O (50 : 50 : 1, v/v/v) solution (abbreviated as "mixed solvent") was used for the measurements of the kQ values for Cars (30).…”
mentioning
confidence: 99%
See 1 more Smart Citation